منصة للاماكن السياحية في فلسطين - عايش, يزن; مناصرة, خالد (جامعة بوليتكنك فلسطين - تسويق)
There are many websites and names on the social media that are interested in tourism and tourist places in Palestine. Thus we built our website "epaltour" which connects the tourists with the targeted places, such as hotels, resturants, or holy places. The website provides the abilty to be in contact with the tourists for the managers of these places, so they can give them informmations or offers that the tourist may need. Our website "epaltour" includes many competitve properties, such as the ability to compare survices with each other to choose the best for you, and 24 hours/7 days technical support. In addition to that, the website allows the presentation and marketing of these services following modern strategies in order to give the targeted group of people the best value in the exact time and place. We also built our website according to the recommendations of the targeted group, so they can easily search it to check what is best and important for them with very simple clicks.
" Epaltour
no of pages 101 , تسويق الكتروني 2020
Keywords: التسويق الالكتروني - السياحة